Peculiarities of the Formation of Public Art in the Late 20th and the Early 21st Centuries: Conceptual Content and Terminology - Yeryomka, Daria (HUDPROM: The Ukrainian Art and Design Journal, 2023)
The article is devoted to the study of the conceptual and terminological essence of public art, an artistic phenomenon in the art of the late twentieth and early twenty-first centuries. The article reveals the characteristic features of public art and related areas of “street” art, primarily street art and graffiti art, phenomena that share a common space with public art in the city and at the same time use identical artistic mechanisms of addressing the audience. The universality of public art’s position in the extremely saturated visual field of contemporary art is comprehended. The constant growth of forms and development of public art techniques significantly actualizes the issue of studying its conceptual and terminological nature. The author of the article proposes to consider public art as a synthetic artistic phenomenon, the formation of which is associated with attempts to interpret various aspects of urban culture and give it an artistic assessment. Based on the analysis of the historiography of the problem, two stages can be traced in the definition of public art. At the first stage (the1980s – 1990s), there were attempts to define the main conceptual field of public art, to coordinate its coexistence with other forms of urban artistic practices. During the second stage (the 2000s – 2010s), the analysis of the internal genealogy of public art and the study of its artistic properties continues. The historical genealogy of public art shows constant attempts to define its own artistic boundaries. This process has a mediative form, as it requires reconciliation of various points of view: artists, customers, city authorities, and viewers. From our point of view, this feature gives grounds to define the artistic essence of public art as an art of mediation. The materials in this article provide many different examples of public art that clearly reveal some of the artistic features of this artistic phenomenon.